IMA-FLADRC-Based Electric-Driven High-Speed Maize Precision Seeding Control Strategy and System - Song Wang; Shujuan Yi; Bin Zhao; Yifei Li; Dongming Zhang; Tao Chen; Wensheng Sun (IEEE Access)
Under high-speed seeding conditions, the accuracy and synchronization of the guiding and seeding motors are critical to seed spacing uniformity. This study develops an electric-driven high-speed maize precision seeding control system, establishing kinematic models for the seeding and guiding motors relative to operating speed. An Improve Mayfly Algorithm-Fuzzy Linear Active Disturbance Rejection Control (IMA-FLADRC)-based control strategy is proposed, integrating a fuzzy algorithm to adaptively adjust the proportional coefficient of the Linear State Error Feedback (LSEF) and optimizing key parameters using an IMA, enhancing system adaptability and robustness. Simulation results show that the IMA-FLADRC-based guiding motor achieves no overshoot or static error, with an adjustment time of 1.121s, a maximum disturbance error of 12.016 r/min, and a disturbance recovery time of 0.008s, while the seeding motor exhibits no static error, minimal overshoot of 0.059%, an adjustment time of 0.374s, a maximum disturbance error of 2.563 r/min, and a disturbance recovery time of 0.003s, outperforming four other strategies. Speed accuracy tests confirm that at 12–16 km/h, the dual-motor speed deviation ratio remains below 1.54%. Bench tests under varying speeds and theoretical seed spacing conditions indicate that the IMA-FLADRC achieves an average seed spacing variation coefficient of 9.10%, with reductions of 2.35, 1.60, and 0.85 percentage points compared to LADRC, FLADRC, and MA-FLADRC, respectively. The average seed spacing deviation is 2.56 mm, the lowest among all strategies. These findings demonstrate that the IMA-FLADRC-based control system ensures highly synchronized dual-motor operation, significantly enhancing seeding uniformity.